Penerapan Logika ANFIS Sistem Penilaian Kinerja Dosen Pada Tri Dharma dan Perilaku Kerja - Kiswanto Kiswanto; Benny Wijaya Benny; Yurindra Yuri; Marini Mar; Sarwindah Sarwindah; Supardi Supardi (Universitas Diponegoro, 2022)
This research is motivated by several problems related to the not-yet optimal implementation of the performance assessment of tri dharma lecturers and work behavior on the ISB Atma Luhur campus. The importance of this research is because the tri dharma lecturer performance appraisal system and work behavior are useful for study program accreditation and university accreditation. The purpose of this study is to make lecturers responsible for the tri dharma and work behavior. The method used in this study is the ANFIS logic method. The results of this study are in the form of a lecturer's report card or a lecturer's performance assessment for one semester issued by SPMI. The variables used are education and teaching 40%, research 20%, dedication 10%, and work behavior 30%. The main result is the report card for each lecturer. The main finding from the lecturers' report cards, a decision can be made for SPMI to reprimand lecturers whose lecturers report cards to fall into the category of